Production potential of Lahangaon soil series for rice based cropping sequences in riverine floodplains of northeastern India - Singh, Dharam; Bhaskar, B.P.; Baruah, U.; Sarkar, Dipak (Annals of Agricultural Research, 2014)
On farm field experiments during 2005-2008 were conducted on Lahangaon soil series (Aeric Fluvaquents) of Jorhat district (Assam) to evaluate production potential, resource use efficiency and benefit cost ratio of four rice-based cropping systems (rice-fallow, rice -potato, rice -pea and rice-mustard) at two management levels i.e. farmers practice (FP) and recommended package of practices (RPP). The cropping system productivity in terms of rice equivalent yield (REY) of rice-potato cropping system (155.9 q ha-1) with RPP was found economically significant followed by rice-pea (141.0 q ha-1) and rice- mustard. Thus, rice-potato system is most productive, sustainable, resource use efficient and remunerative cropping system followed by rice-pea and rice mustard systems. RPP performed better over FP in all cropping systems.